2002
DOI: 10.1590/s0100-67622002000600001
|View full text |Cite
|
Sign up to set email alerts
|

Semeadura direta de canafístula (Peltophorum dubium (Spreng.)taub. No enriquecimento de capoeiras

Abstract: O presente trabalho teve por objetivo avaliar o comportamento da canafistula (Peltophorumdubium), em semeadura direta a campo, em área de capoeira originada após o abandono do local utilizado com cultivos agrícolas sucessivos. No local foram roçadas faixas de 1,5 m, a cada 3 m. A semeadura foi realizada em setembro de 1997. Visando proteger os pontos semeados, foram utilizados diferentes tipos de protetores (copos de plástico e copos de papel, sem fundo e laminado de madeira), fixados sobre os pontos semeados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 3 publications
(4 reference statements)
1
15
0
6
Order By: Relevance
“…(1995) reports that the used physical protector, a plastic cup of 250 ml, without bottom and with the largest circumference of the circle to the face down, promoted an increase in the tax of germination. Mattei and Rosenthal (2002), notice that protectors as plastic cups and paper cups, without bottom, contributed in the initial emergence and in the establishment of the canafistula seedlings evaluated at 18 months after sowing. Conflicting results were observed by Ferreira et al (2007), in a study with Senna multijuga, observed significant effect for the physical protector, which correspond to transparent plastic pots of 500 ml without bottom, putted above the sowing points.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…(1995) reports that the used physical protector, a plastic cup of 250 ml, without bottom and with the largest circumference of the circle to the face down, promoted an increase in the tax of germination. Mattei and Rosenthal (2002), notice that protectors as plastic cups and paper cups, without bottom, contributed in the initial emergence and in the establishment of the canafistula seedlings evaluated at 18 months after sowing. Conflicting results were observed by Ferreira et al (2007), in a study with Senna multijuga, observed significant effect for the physical protector, which correspond to transparent plastic pots of 500 ml without bottom, putted above the sowing points.…”
Section: Resultsmentioning
confidence: 96%
“…In this way, the use of physical protectors allowed with direct seedling become relevant, once it can cause the reduction seeds and seedlings predation. Besides, the advantage of its interference in germination and establishment of species created a favorable microenvironment (Ferreira, 2002;Mattei and Rosenthal, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A aceleração da germinação de sementes para recobrimento do solo, via semeadura direta em recuperação de áreas degradadas, é imprescindível para que as sementes germinem prontamente e sincronicamente, permitindo uma eficiente implantação de coberturas vivas (MATTEI;ROSENTHAL 2000;SANTOS et al, 2012) Considerando os resultados obtidos, nota-se que as sementes de S. obtusifolia não apresentaram dormência tegumentar. Entretanto, recomenda-se a imersão de suas sementes em água a 75 °C, seguida de embebição por 18 horas, para acelerar o recobrimento do solo através de semeadura direta em projetos comerciais de restauração de áreas degradadas.…”
Section: Discussionunclassified
“…Unlike the condition on the nursery, the lethal agents of the field conditions are not under control (Mattei and Rosenthal, 2002;Woods and Elliot, 2004). Therefore, auxiliary procedures also must be tested, for instance straw and forest litter addition, physical protectors, organic manure supply and weed management.…”
Section: Introductionmentioning
confidence: 99%